Identification of pathological complete response after neoadjuvant chemotherapy for breast cancer: comparison of greyscale ultrasound, shear wave elastography, and MRI. Issue 10 (October 2018) - Evans, A.; Whelehan, P.; Thompson, A.; Purdie, C.; Jordan, L.; Macaskill, J.; Henderson, S.; Vinnicombe, S.
Abstract : Aim: To assess the value of post-treatment shear-wave elastography (SWE) parameters (maximum stiffness [Emax], mean stiffness [Emean], and standard deviation [SD]) compared to greyscale ultrasonography (US) and magnetic resonance imaging (MRI) in identifying pathological complete response (pCR) to neoadjuvant chemotherapy (NACT) in breast cancer. Materials and methods: In a prospective cohort study, 80 patients receiving NACT for breast cancer underwent baseline and post-treatment US, SWE, and MRI examinations. Four SWE images in two orthogonal planes were obtained. Maximum greyscale US diameter and maximum diameter of lesion enhancement on MRI were measured. Percentage reductions between baseline and post-treatment scans were calculated for MRI and greyscale US diameter, and Emean, Emax, and SD. The percentage reduction in Emean and US diameter were also analysed as a combination. Analysis was undertaken using receiver operating characteristic (ROC) curves and the chi-squared test. Results: pCR occurred in 21 of 80 (26%) women. The area under the ROC curve (AUC) for pCR of percentage reductions in Emean, Emax, SD, and greyscale US diameter were 0.89, 0.85, 0.75, and 0.86, respectively. The combination of percentage reductions in Emean and greyscale ultrasound diameter yielded an AUC of 0.92, which is similar to the AUC for MRI of 0.96 ( p= 0.28). Conclusions: SWE combined with greyscale US shows promise for end-of-treatment identification of response to NACT in women with breast cancer, with accuracies similar to breast MRI. This technique could be used to inform surgical decision-making after NACT. Highlights: A reduction in lesion stiffness at SWE at the end NACT predicts response. Combining the reduction in stiffness and US diameter increases prediction. The combination of reduction in stiffness and US diameter performs similarly to MRI.